EVALUATION OF ELECTRONIC LIMITED STAY NOTIFICATION SYSTEMS IN THE IMMIGRATION OFFICE CLASS I PEKANBARU - ROCKY SIMANJUNTAK (Polteknik Imigrasi, 2020)
Presidential Regulation Number 20 of 2018 concerning the Use of Foreign Workers as a trimmer of bureaucracy so that Foreign Workers who will come to Indonesia have the licensing process not as complicated as before. However, the reality in the field still finds some systemic problems that occur in the ITAS extension process, including: Electronic ITAS notification sending that does not go to the sponsor's email and has to be resent and the network when taking Biometrics (taking photos and fingerprints) is slow and the Biometric Matching System (BMS) to the center used by all applications requiring biometric checks is also slow. This certainly hinders immigration officers from issuing ITAS. System problems that occur include: Electronic ITAS notification sending that does not go to the sponsor's email and has to be resent and the network when taking Biometrics (taking photos and fingerprints) is slow and Biometric Matching System (BMS) to the center used by all applications requires slow biometric checks too. This certainly hinders immigration officers from issuing ITAS.